Evaluation of MRI-compatible pneumatic muscle stepper motors - Odenbach Robert (Current Directions in Biomedical Engineering, 2019)
The automation of instruments and tools (e.g. bone drill) or robotic devices (e.g. needle positioning robot for prostate surgery) for use in interventional MRI (iMRI) is still challenging due to a lack of accurate, affordable and completely metal-free actuators and motors. Inspired by biological muscles, a bionic equivalent known as the fluid muscle actuator (which can be operated pneumatically or hydraulically) is well-known in the mechanical engineering industry. Fluid muscle actuators have multiple beneficial characteristics: they are simple, self-returning, low-friction and can produce relatively high actuation forces at low diameters and pressures. We present two novel designs for metal-free, pneumatic stepper motors for potential application in iMRI. Our stepper motors are powered by simple pneumatic muscles, which are assembled from low-cost off-the-shelf components. Besides, the components of the stepper motor demonstrators were 3Dprinted using a stereolithographic additive manufacturing process (SLA printing). We evaluate the effect of pneumatic muscle length on contractile force and length. Our results demonstrated the functional feasibility of the pneumatic muscle-powered and fully MRI-compatible stepper motor designs. In a next step, we will optimize the motor´s design, characterize their performance and reliability, and use the stepper motors to power a micropositioning device in iMRI-phantom tests.